Soul Survivors - Carpenter, Stephen; Hamilton, Allen; Angela Featherstone; Casey Affleck; Eliza Dushku; Luke Wilson; Wes Bentley; Melissa Sagemiller (USA Lost Soul Productions, 2001)
College freshman Cassandra ""Cassie"" (Melissa Sagemiller) steps into a nightmare of otherworldly visitations after surviving a devastating car accident. Haunted by a grim reaper of a far different kind, her only hope is to cling to chance encounters with her lost love Sean (Casey Affleck) and the aid of a mysterious young priest named Father Jude (Luke Wilson). It is the spirit of Sean, her soul mate, who guides her to love, but it is her friends Matt (Wes Bentley), Annabel (Eliza Dushku) and Annabel's morose friend Raven (Angela Featherstone) who try to draw her to the dark side.
A co-ed is caught between the world of the living and the dead.
Stephen Carpenter
Languages : English, Turkish, French Subtitles : English, French, Spanish
Keywords: Horror; Thriller; Drama